On the control of dispersion interactions between biological membranes and protein coated biointerfaces - Blackwell, Robert; Hemmerle, Arnaud; Baer, Andreas; Späth, Matthias; Peukert, Wolfgang; Parsons, Drew; Sengupta, Kheya; Smith, Ana-Suncana (Journal of Colloid and Interface Science, 2021)
Hypothesis: Interaction of cellular membranes with biointerfaces is of vital importance for a number of medical devices and implants. Adhesiveness of these surfaces and cells is often regulated by depositing a layer of bovine serum albumin (BSA) or other protein coatings. However, anomalously large separations between phospholipid membranes and the biointerfaces in various conditions and buffers have been observed, which could not be understood using available theoretical arguments. Methods: Using the Lifshitz theory, we here evaluate the distance-dependent Hamaker coefficient describing the dispersion interaction between a biointerface and a membrane to understand the relative positioning of two surfaces. Our theoretical modeling is supported by experiments where the biointerface is represented by a glass substrate with deposited BSA and protein layers. These biointerfaces are allowed to interact with giant unilamellar vesicles decorated with polyethylene glycol (PEG) using PEG lipids to mimic cellular membranes and their pericellular coat. Results: We demonstrate that careful treatment of the van der Waals interactions is critical for explaining the lack of adhesiveness of the membranes with protein-decorated biointerfaces. We show that BSA alone indeed passivates the glass, but depositing an additional protein layer on the surface BSA, or producing multiple layers of proteins and BSA results in repulsive dispersion forces responsible for 100 nm large equilibrium separations between the two surfaces.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Biointerfaces; Dispersion forces; Lifshitz theory; Reflection interference contrast microscopy (RICM); Van der Waals interactions